Expression Analysis of GD2 by Immunohistochemistry in Invasive Breast Carcinoma: Clinical and Pathologic Correlation. Issue 2 (February 2022) - Zhong, Elaine; Brogi, Edi; D'Alfonso, Timothy M.; Wen, Hannah; Frosina, Denise; Cheung, Nai-Kong; Jungbluth, Achim A.; Ross, Dara S.
Abstract : The glycosphingolipid disialoganglioside GD2 is a cell surface–associated antigen expressed on tumors of neuroectodermal origin that serves as a target of immunotherapy in select cancer types. Information about the expression of GD2 in breast cancer is limited. In the present study, we investigate the utility of GD2 as a potential biomarker for targeted treatment. The study cohort consists of 386 breast carcinomas of several histologic types. GD2 expression was assessed in both whole tumor sections and tissue microarrays with anti-GD2 3F8 monoclonal antibody immunohistochemistry and correlated with clinicopathologic features and survival outcomes. A total of 134 (35%) breast carcinomas were positive for GD2, with a median H -score of 100. 3F8 staining displayed granular and predominantly cytoplasmic or perinuclear patterns, which was confined to the neoplastic tissue in nearly all cases. GD2 positivity was significantly associated with tumor histologic type ( P =0.0015), low grade ( P <0.0001), estrogen receptor positivity ( P <0.0001), low stage ( P =0.0014), and multifocality ( P =0.022). Event-free survival and overall survival of patients with GD2-positive and GD2-negative tumors were not significantly different. Our results support further assessment of GD2 using the 3F8 antibody as a predictive and prognostic biomarker in breast cancer.